2018
DOI: 10.4238/gmr18083
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Evaluation of genetic variability to form heterotic groups in popcorn

Abstract: In view of the narrow genetic base of popcorn, probably due to its evolution by selection from flint maize types alone, knowledge about genetic divergence is imperative for the formation of heterotic groups. Thus, our objective was to identify heterotic groups of popcorn lines; we did so by exploiting the representative genotype collection of the Active Popcorn Germplasm Bank of the State University of Northern Rio de Janeiro. Thirty-eight popcorn genotypes from different origins were analyzed by two methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In a first instance, crosses between parents with a good performance for grain yield and its components (P3, P6, and P7 with L71), may be promising. In genetic diversity studies, estimated by microsatellite markers (SSR-EST), the largest genetic distances were found between P6 and L71 [8,45], indicating a better chance for allelic complementation. Hybrids resulting from the combination of these parents can have high performance for both popping expansion and grain yield.…”
Section: Genetic Merit Of Parents and Theoretical Limits Of Selectionmentioning
confidence: 99%
“…In a first instance, crosses between parents with a good performance for grain yield and its components (P3, P6, and P7 with L71), may be promising. In genetic diversity studies, estimated by microsatellite markers (SSR-EST), the largest genetic distances were found between P6 and L71 [8,45], indicating a better chance for allelic complementation. Hybrids resulting from the combination of these parents can have high performance for both popping expansion and grain yield.…”
Section: Genetic Merit Of Parents and Theoretical Limits Of Selectionmentioning
confidence: 99%
“…Consequently, the exploitation of variability in popcorn becomes fundamental to access so far unexplored sources of drought tolerance in plant breeding. For this, the North Fluminense State University "Darcy Ribeiro" (UENF) has a germplasm collection containing accessions from temperate and tropical climatic adaptated regions of Latin America, as well as inbred lines from improved elite materials in Brazil [13]. In this regard, a better understanding of the morphoagricultural and physiological responses of plant genetic resources is required and some strategies to optimize plant selection in water-deficit environments are proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Inbreds with contrasting popping attributes can be used to identify the loci for further improvement by developing segregating mapping populations. Vittorazzi et al (2018) has reported sufficient genetic variability at phenotypic and genotypic levels among the 38 popcorn genotypes. Babu et al (2006) mapped QTLs for popping quality traits using popcorn × flint corn, while Lu et al (2003) and Jain-Poster and Thomas (2015) identified QTLs through mapping population developed from popcorn × dent corn.…”
Section: Utilization In Popcorn Breedingmentioning
confidence: 99%
“…The recent initiatives under the maize breeding programme in India have led to the development of new sub-tropically adapted diverse popcorn inbreds from exotic-and indigenous-sources. Characterization of these newly available inbreds and understanding their genetic relationships therefore hold immense significance for their utilization in the breeding programme (Devi et al 2017, Vittorazzi et al 2018). Molecular markers have often been utilized for accurate measurement of genetic relationship due to their abundance, whole genome coverage and environment neutral behavior.…”
mentioning
confidence: 99%